2020
DOI: 10.1186/s13071-020-04177-0
|View full text |Cite
|
Sign up to set email alerts
|

Blood parasites in vectors reveal a united blackfly community in the upper canopy

Abstract: Background: The behaviour of blood-sucking arthropods is a crucial determinant of blood protozoan distribution and hence of host-parasite coevolution, but it is very challenging to study in the wild. The molecular identification of parasite lineages in vectors can be a useful key to understand the behaviour and transmission patterns realised by these vectors. Methods: In this study, we collected blackflies around nests of three raptor species in the upper forest canopy in central Europe and examined the presen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 29 publications
(61 reference statements)
1
21
0
Order By: Relevance
“…Our current results do not confirm if the adaptations connected with carrion-feeding lifestyle and gut microbiome suppress transmission, or otherwise affect the blood parasite fauna. In conjunction with the patterns found in previous studies on raptor and non-raptor scavengers, it appears probable that habitat features play an important role in the transmission of blood parasites [26,62]. An additional role in the specific features of the host immunity needs to be further explored.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Our current results do not confirm if the adaptations connected with carrion-feeding lifestyle and gut microbiome suppress transmission, or otherwise affect the blood parasite fauna. In conjunction with the patterns found in previous studies on raptor and non-raptor scavengers, it appears probable that habitat features play an important role in the transmission of blood parasites [26,62]. An additional role in the specific features of the host immunity needs to be further explored.…”
Section: Discussionmentioning
confidence: 68%
“…However, vectors mostly seek hosts close to their emergence and oviposition sites, which for blackflies are flowing water bodies [ 44 , 45 ]. Additionally, some vector species appear to have quite specific habitat and less specific host preferences, e.g., using cavities or keeping close to shade and intact foliage, and even preferring specific heights in the trees [ 26 , 46 ]. At the same time, flying in hot and open areas may strongly increase the danger of desiccation without compensating with secure encounters with hosts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it is likely that feral pigeons could have acted as a reservoir and blackflies transmitted the lineages from feral pigeons to woodpigeons and vice versa. While Scaglione et al ( 2015 ) states that Leucocytozoon parasites are not routinely found in pigeons, a study sampling blackflies in Central Europe showed pigeons to be one of the main targets of ornithophilic blackflies (Chakarov et al 2020 ). High rates of Leucocytozoon in the sampled woodpigeons may have been favoured by the opportunities for transmission that the woodpigeons offered (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, only few studies have presented data on the prevalence and diversity of haemosporidian parasites in closely related bird species. Differences in prevalence between species are associated with several factors and the interactions between those, including life-history traits and ecology of the hosts and vectors, parasite characteristics and environmental conditions, that may affect the activity of vectors and the development of parasites (Sol et al 2000 ; Gupta et al 2011 ; Quillfeldt et al 2011 ; Hellard et al 2016 ; Chakarov et al 2020 ; Ciloglu et al 2020b ; Ellis et al 2020 ). Also different behavioural characteristics (e.g.…”
Section: Introductionmentioning
confidence: 99%